KARAKTERISTIK IBU DAN PEMBERIAN ASI EKSKLUSIF - Purnama, Nicky; Wiyati, Nining; Widyasih, Hesty (Jurnal Kesehatan Ibu dan Anak, 2016)
Exclusive breastfeeding is an essential program which is quite hard to develop since it is related to social problems of thecommunity. Till 2012, in the Special Teritory of Yogyakarta exclusive breast feeding had reached up to 49.5%. In 2011exclusive breastfeeding in Bantul reaches up to 42.3%. 10.3% is recorded at Puskesmas Jetis I, Bantul, in the same year.There are a lot of factors that influence the mothers' behavior for giving breastfeeding exclusively, such as age, education,occupation, parity and family income. They all constitute the characteristics of the mothers giving exclusive breastfeeding.This research is conducted to investigate the correlation between the mother'scharacteristics and exclusive breastfeeding atPuskesmas Jetis I, Bantul, (2013) as the area of sample collection. This research is an analytic study using a cross sectionaldesign. The study is conducted at the Puskesmas Jetis I, Bantul, in 2013. The subjects are mothers with infants aged 6-24months old with the total number of 161 mothers. The measuring instrument used is questionnaire. The technique used toanalyze is the Chi-Square. The result of this study shows that the majority mothers at the Puskesmas Jetis I do not giveexclusive breastfeeding (82.6%). The result of bivariate analysis shows the mother's age (p value: 0.00). Infact, there iscorrelation between mother's age and exclusive breastfeeding. For mother's education (p value: 0.00), there is correlationbetween mother's education and exclusive breastfeeding. For mother's occupation (p value: 0.305), there is not anycorrelation between mother's occupation and exclusive breastfeeding. For parity (pvalue: 0.309) , there is not any correlationbetween parity and exclusive breastfeeding. At last, for family income (p value: 0.00) ), there is correlation between familyincome and exclusivebreastfeeding. The conclusion is that thecharacteristics of mothers related to exclusive breastfeedingareage, education, andfamily income.